The serotonin receptor 2A (HTR2A) rs6313 variant is associated with higher ongoing pain and signs of central sensitization in neuropathic pain patients. (3rd December 2020) - Sachau, Juliane; Bruckmueller, Henrike; Gierthmühlen, Janne; Magerl, Walter; May, Denisa; Binder, Andreas; Forstenpointner, Julia; Koetting, Judith; Maier, Christoph; Tölle, Thomas R.; Treede, Rolf‐Detlef; Berthele, Achim; et al.
Abstract: Background: The serotonin receptor 2A (HTR2A) has been described as an important facilitation mediator of spinal nociceptive processing leading to central sensitization (CS) in animal models of chronic pain. However, whether HTR2A single nucleotide variants (SNVs) modulate neuropathic pain states in patients has not been investigated so far. The aim of this study was to elucidate the potential association of HTR2A variants with sensory abnormalities or ongoing pain in neuropathic pain patients. Methods: At total of 240 neuropathic pain patients and 253 healthy volunteers were included. Patients were phenotypically characterized using standardized quantitative sensory testing (QST). Patients and controls were genotyped for HTR2A g.‐1438G > A (rs6311) and c.102C > T (rs6313). Genotype‐related differences in QST parameters were assessed considering QST profile clusters, principal somatosensory components and sex. Results: There was an equal distribution of rs6313 and linked rs6311 between patients and controls. However, the rs6313 variant was significantly associated with a principal component of pinprick hyperalgesia and dynamic mechanical allodynia, indicating enhanced CS in patients with sensory loss (−0.34 ± 0.15 vs. +0.31 ± 0.11 vs., p < .001). In this cluster, the variant allele was also associated with single QST parameters of pinprick hyperalgesia (MPT, +0.64 ± 0.18 vs. −0.34 ± 0.23 p = .002; MPS, +0.66 ± 0.17 vs. −0.09 ± 0.23, p = .009) and ongoing pain was increased by 30%. Conclusions: The specific association of the rs6313 variant with pinprick hyperalgesia and increased levels of ongoing pain suggests that the HTR2A receptor might be an important modulator in the development of CS in neuropathic pain. Significance: This article presents new insights into serotonin receptor 2A‐mediating mechanisms of central sensitization in neuropathic pain patients. The rs6313 variant allele was associated with increased mechanical pinprick sensitivity and increased levels of ongoing pain supporting a contribution of central sensitization in the genesis of ongoing pain providing a possible route for mechanism‐based therapies.